2017
DOI: 10.1007/s11262-017-1452-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of chimeric human cytomegalovirus vaccine candidates derived from strains Towne and Toledo

Abstract: Human cytomegalovirus (HCMV) is an important opportunistic pathogen in immunocompromised patients and a major cause of congenital birth defects when acquired in utero. In the 1990s, four chimeric viruses were constructed by replacing genome segments of the high passage Towne strain with segments of the low passage Toledo strain, with the goal of obtaining live attenuated vaccine candidates that remained safe but were more immunogenic than the overly attenuated Towne vaccine. The chimeras were found to be safe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…As an attempt to improve the immunogenicity provided by Towne, four Towne/Toledo genome chimeras have been generated by substituting portions of the Toledo strain UL/b’ region with those of the Towne strain [97]. When tested in phase I clinical trials, the Towne/Toledo chimeras were attenuated relative to Toledo [98], showed acceptable safety profiles, and stimulated immune responses similar to those conferred by Towne [99].…”
Section: Congenital Cytomegalovirus Prophylactic Vaccinesmentioning
confidence: 99%
“…As an attempt to improve the immunogenicity provided by Towne, four Towne/Toledo genome chimeras have been generated by substituting portions of the Toledo strain UL/b’ region with those of the Towne strain [97]. When tested in phase I clinical trials, the Towne/Toledo chimeras were attenuated relative to Toledo [98], showed acceptable safety profiles, and stimulated immune responses similar to those conferred by Towne [99].…”
Section: Congenital Cytomegalovirus Prophylactic Vaccinesmentioning
confidence: 99%
“…What impact this would have on the potential efficacy of a congenital CMV vaccine is unclear. The recently reported DNA sequence analysis of the Towne-Toledo chimeras should aid in elucidating the molecular basis for the observed differences in immunogenicity seen in this clinical trial, as well as in identifying potential genetic markers conferring attenuation (101).…”
Section: Live Attenuated and "Disc" Vaccinesmentioning
confidence: 99%
“…These chimeras showed strong safety profiles and induced conventional CD8 + T cell responses, but showed differences in immunogenicity between chimeras 74 . Unfortunately, DNA sequencing analysis showed that all four chimeras had disrupted copies of the UL128 gene and so could not express WT PC 77 . However, this sequencing data may provide useful information for understanding how genetic differences between attenuated viruses correlate with differences in immunogenicity between chimeras, which could inform future vaccine design.…”
Section: Vaccines Against Hcmv Are Still In Developmentmentioning
confidence: 99%